Cognitive Insights from Emotional Intelligence: A Systematic Review of EI Models in Educational Achievement - Evgenia Gkintoni; Ioannis Dimakos; Georgios Nikolaou (Emerging Science Journal, 2024)
Objectives: This study aims to investigate the relationship between Emotional Intelligence (EI) and academic achievement within educational settings. It seeks to determine how different EI models”specifically, Ability EI and Trait EI”impact students' academic performance, behavior, engagement, and motivation. The goal is to provide insights that can guide the integration of EI into educational practices to foster a more supportive and effective learning environment. Methods/Analysis: The study is based on a systematic review of sixty-four (64) peer-reviewed studies published between 2016 and 2023. These studies include randomized controlled trials (RCTs), longitudinal studies, and meta-analyses. The selected studies were analyzed to explore the effects of EI on various academic outcomes, including performance, behavioral engagement, and motivation. Findings: The analysis reveals that both Ability EI and Trait EI are positively associated with academic success. These models of EI appear to contribute significantly to the development of key skills such as emotional control, empathy, and problem-solving, which in turn support effective classroom management and academic achievement. The findings suggest that incorporating EI into educational curricula can lead to improved communication, better problem-solving abilities, and enhanced relationships between students and faculty. These improvements can create a more conducive learning environment and enhance overall academic outcomes. Novelty/Improvement: This study adds to the existing literature by offering a comprehensive review of recent studies that examine the role of EI in academic settings. It highlights the importance of implementing EI-focused interventions and curricula in schools, emphasizing the practical implications for educators and policymakers. Doi: 10.28991/ESJ-2024-SIED1-016 Full Text: PDF